Seleksi probiotik Lactobacillus sp. dari usus ikan mas (Cyprinus carpio) potensial untuk akuakultur - Bella, Sintia S.; Manoppo, Henky; Undap, Suzanne L.; Tumbol, Reiny A.; Ngangi, Edwin L. A. (Universitas Sam Ratulangi, 2020)
The aimed of the study was to isolate and select the probiotic Lactobacillus from carp intestine potential for use in aquaculture. Carp as a source of probiotics with a size of about 200 g was Â taken from the Center for Fish Hatchery and Disease Control (BP3I), Tateli. After aseptic surgery, the intestine was separated and cleaned, weighed as much as 1 g, put in a mortar and crushed until smooth. The scoured results were put into a tube and added 9 ml NaCl to get a ratio of 1:10. The tube that already contains intestinal scouring was then centrifuged at a speed of 1000 RPM for 10 minutes. The centrifugation process was carried out 2 times to get the supernatant that has been cleared of debris. The supernatant was removed and diluted to obtain a concentration of 10-2 Â to 10-3. The solution was then spread on MRS (De Man Rogosa and Sharpe Agar) media and incubated at 28oC in the Incubator for 24-48 hours. The bacteria that grew in culture fmedia was reisolated several times to get a single pure colony.. The pure colonies were propagated in the same media to be further identified through gram staining, biochemical, proteolytic, amylolytic, cellulolytic, antibiotic resistance, antagonistic, pathogenicity tests. The results of the isolation obtained the characteristics of a colony of milky white color, round and convex with long cells, gram-positive and confirmed based on biochemical tests as Lactobaccilus sp. The bacterium also had proteolytic, amylolytic, cellulolytic, antagonistic, antibiotic-sensitive activity that were characterized by the formation of clear zones in the area around probiotic discs, and did not cause death either as a disease or as a result of poisoning. Thus it can be concluded that Lactobaccilus sp. isolated from carp intestines can be used as probiotics for cultivation.